Urgency of The Village of Financial Management Under The Government Regulations - Muchamad Taufiq; Mimin Yatminiwati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
This study aims to conduct a study on Application of Financial Statements village in the subdistrict Klakah Sruni Village Government Lumajang has been presented by Regulation No. 113 of 2014 on the management of village finances. This study uses qualitative research descriptive. Types and sources of data used in this study consisted of secondary data such as data collection in the form of publications, reports, documents, and other documents pertinent to this research. While primary data obtained directly from the village government staff Sruni. The results showed overall in fiscal years 2016 and 2017 the village has implemented financial management Sruni village well guided by the Minister Regulation No. 113 of 2014 concerning the financial management of the village.